Evaluating the food colors in traditional confectionaries and beverages in Shiraz city - Zahra Gholami; Roya Firouzi; Marzieh Rashedinia (Shiraz University of Medical Sciences, 2021)
Food colorants are addictive substances that are creating a good and attractive appearance to foods The synthetic food dyes have been strictly controlled by the legislation in the world. Artificial food colorants may cause harmful effect on human health. As the safety of substances in some traditional food products is questionable, this study was conducted to evaluate the type and frequency of the food colorants in traditional confectionery, syrup and fruit juice, in Shiraz, Iran. Totally 806 samples were collected during 2017 to 2019. Analysis of samples was done using thin layer chromatography method according to the Iranian national standard. Results showed that 51.61% of samples did not have any additive color, and 48.39 % of samples contained artificial colors that should not be used in sweets and are not permitted for use according to the Iranian national standards. Tartrazine and Quinoline Yellow were the most frequently used as non- permitted food color. Therefore, about half of the samples are non-consumable. Use synthetic food dyes in a high percentage of supplied products in unauthorized places needs the necessity to increase supervision of relevant officials and raise the consumer awareness about the permitted food colors and adverse and toxic effects of forbidden colors.